RANCANG BANGUN SISTEM INFORMASI MAINTENANCE ASETBERGERAK BERBASIS WEBSITE PADA PT PERTAMINA PATRA NIAGA DPPU SSK II PEKANBARU - Muhammad Abigail Athallah (2023)
The problems faced by PT Pertamina Patra Niaga DPPU SSK II Pekanbaru, related to irregular data management, unresponsive reporting performance, business processes not running smoothly, inefficient system procedures, and service dissatisfaction, can slow down the flow of activities of the positions involved. Therefore, the solution that is given is the design of website based movable assets maintenance information system in PT Pertamina Patra Niaga DPPU SSK II Pekanbaru. The purpose of this research is to design the website based movable assets maintenance information system in PT Pertamina Patra Niaga DPPU SSK II Pekanbaru. The benefit of the research is to facilitate RSD department to report crashes to maintenance department in order to fix immediately. The method that is used by this research is the waterfall method. The results of this research are in the form of a website-based movable asset maintenance information system that can process data and reports smoothly, the performance of the reporting process becomes responsive, business processes become smooth, improves data security protection, system procedures become more efficient, and service satisfaction with the presence of login features, manage checklist books, add damage data, verify repairs data, and manage movable assets.